Coculture of Primary Motor Neurons and Schwann Cells as a Model for In Vitro Myelination - Hyung, Sujin; Lee, Bo Yoon; Park, Jong-Chul; Kim, Jinseok; Hur, Eun-Mi; Suh, Jun-Kyo Francis (NATURE PUBLISHING GROUP, 2015)
A culture system that can recapitulate myelination in vitro will not only help us better understand the mechanism of myelination and demyelination, but also find out possible therapeutic interventions for treating demyelinating diseases. Here, we introduce a simple and reproducible myelination culture system using mouse motor neurons (MNs) and Schwann cells (SCs). Dissociated motor neurons are plated on a feeder layer of SCs, which interact with and wrap around the axons of MNs as they differentiate in culture. In our MN-SC coculture system, MNs survived over 3 weeks and extended long axons. Both viability and axon growth of MNs in the coculture were markedly enhanced as compared to those of MN monoculture. Co-labeling of myelin basic proteins (MBPs) and neuronal microtubules revealed that SC formed myelin sheaths by wrapping around the axons of MNs. Furthermore, using the coculture system we found that treatment of an antioxidant substance coenzyme Q10 (Co-Q10) markedly facilitated myelination.
Keywords: COENZYME Q(10); OLIGODENDROCYTE; DIFFERENTIATION; REGENERATION; MOTONEURONS; METABOLISM; MECHANISMS; RILUZOLE; INJURY